If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(m + -9) + 3m = 7m + 43 Reorder the terms: 9(-9 + m) + 3m = 7m + 43 (-9 * 9 + m * 9) + 3m = 7m + 43 (-81 + 9m) + 3m = 7m + 43 Combine like terms: 9m + 3m = 12m -81 + 12m = 7m + 43 Reorder the terms: -81 + 12m = 43 + 7m Solving -81 + 12m = 43 + 7m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-7m' to each side of the equation. -81 + 12m + -7m = 43 + 7m + -7m Combine like terms: 12m + -7m = 5m -81 + 5m = 43 + 7m + -7m Combine like terms: 7m + -7m = 0 -81 + 5m = 43 + 0 -81 + 5m = 43 Add '81' to each side of the equation. -81 + 81 + 5m = 43 + 81 Combine like terms: -81 + 81 = 0 0 + 5m = 43 + 81 5m = 43 + 81 Combine like terms: 43 + 81 = 124 5m = 124 Divide each side by '5'. m = 24.8 Simplifying m = 24.8
| -11+2m=6(2m+6) | | 5-6=2x-9 | | 2x+7=31-x | | 3k-40=12 | | 3-6=3x | | 3h=-39 | | -3-5=x-6 | | 3x(4x)=300 | | 3=r+11.5-t | | 3(6n-4)=-156 | | -11+2m=6(2n+6) | | 9x-9-x=9-x | | 2x+8+9=2x+8 | | 12-2x+4=4 | | x^3-19x^2+90x+52=0 | | 3k-10=12 | | x-4-x+5-3x=4 | | 8(4-7a)=32+8a | | 2x-4-8-6=4x | | x^2+343= | | 5x+8x-10=6x+4 | | 4n^2+3n+6=0 | | 50-.52x=20 | | 1/5x/1/5=9/1/5 | | 2x+4=x-4 | | 3(2w-1)=9(w+3) | | 3x-28=20+7x | | ln(43)=x | | 8-9=x+3+x | | (2+4x)-(x-9)=26 | | 6.8=h | | 6+2x+11=x+13 |